High-Resolution Melting assays development for discrimination of fungal pathogens causing Grapevine Trunk Diseases - Filipe Azevedo-Nogueira; Ana Gaspar; Sara Barrias; Bruna Costa; Beatriz Silva; Cecília Rego; Paula Martins-Lopes (PLoS ONE, 2025)
Grapevine Trunk Diseases are a set of fungal diseases that mainly affect wood tissues of grapevine, reducing plant fitness and yield. These diseases limit grape production, so producers need to employ several management strategies to avoid great losses. Nevertheless, due to complex etiology and irregular symptom onset that can be influenced by environmental conditions, producers find it difficult to predict outbreaks and thus to implement management practices in a timely manner. Additionally, fungal infections can remain quiescent for several years, colonizing the plant tissues without symptoms, with symptoms emergence usually occurring several years later. Therefore, the identification of infected grapevines is essential for the definition of effective management strategies. The objective of this work was to design a set of assays based on High Resolution Melting that can detect and identify the most common fungal species responsible for four Grapevine Trunk Diseases. The beta-tubulin gene ( Tub2 ) was selected to design an HRM assay, considering a 130 bp amplicon. The assays distinguish ten of the most common fungal species responsible for Botryosphaeria dieback, Esca, Phomopsis dieback and Eutypa dieback, based on difference curve profiles against a known reference, Neofusicoccum parvum . When applied to mixtures of two fungal species, this strategy allowed both the identification and relative quantification of the pathogens. The application of such an analysis to grapevines will allow the assessment of the health status of the vines so informed management practices can be applied. This will also contribute to the reduction of the potentially pathogenic fungal load by the removal of part or the whole infected plant, ultimately reducing viticulture production costs.